2013
DOI: 10.1007/s00520-013-2049-3
|View full text |Cite
|
Sign up to set email alerts
|

The persistence of symptom burden: symptom experience and quality of life of cancer patients across one year

Abstract: PURPOSE The purpose of this longitudinal study was to track the symptom experience in a sample of cancer patients, determine the persistence of cancer symptoms and symptom burden, and examine the relationship between symptoms and QOL over time. METHODS 542 patients provided longitudinal data, completing surveys over a 12 month period. Patients had breast, colorectal, gynecologic, lung or prostate cancer with stage 1, 2 or 3 disease. Surveys included the Memorial Symptom Assessment Scale and the Functional As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
104
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(115 citation statements)
references
References 31 publications
7
104
2
2
Order By: Relevance
“…For QOL specifically, some have examined newly diagnosed older populations with cancer 33,34 or else symptoms in various phases of cancer illness. 3,10,35,36 Our experience supports prior medical informatics reports of Web-based, 37 computer-assisted, 17,28,38,39 tablet 40 or hand-held 11,16,41,42 assessments in various cancer and palliative medicine populations and at other stages of the illness. None of them involved newly diagnosed patients.…”
Section: Discussionsupporting
confidence: 85%
“…For QOL specifically, some have examined newly diagnosed older populations with cancer 33,34 or else symptoms in various phases of cancer illness. 3,10,35,36 Our experience supports prior medical informatics reports of Web-based, 37 computer-assisted, 17,28,38,39 tablet 40 or hand-held 11,16,41,42 assessments in various cancer and palliative medicine populations and at other stages of the illness. None of them involved newly diagnosed patients.…”
Section: Discussionsupporting
confidence: 85%
“…In one of few longitudinal studies using the MSAS in a heterogeneous sample of patients with gynecological cancer, total MSAS scores at enrollment was similar to our findings (0.71 vs 0.69). 2 However, although the total MSAS score temporarily worsened during treatment in our patients, the trend was opposite in the study by Deshields et al, 2 where the women tended to have better scores during treatment before it returned TABLE 3. The MSAS* subscales related to self-rated performance status at enrollment Subscales to enrollment values.…”
Section: Discussioncontrasting
confidence: 72%
“…2 However, most studies assessing symptoms are cross-sectional and include various cancer types, and in studies of a single cancer type, there is an overrepresentation of studies in breast, colorectal, and lung cancer, 22,23 which make comparisons challenging. Of the few self-reported symptom studies that have been conducted in patients with ovarian cancer, our results are comparable with 2 studies using MSAS, where mean numbers of reported symptoms were 11.2 9 and 10.0, 24 compared with 10.7 in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the many challenges in cancer survivorship are longterm or permanent physical and mental health problems, which often occur as a result of diagnosis and treatment [1,2]. For example, cancer survivors (CSs) may experience fatigue, pain and cognitive problems, long after treatment has been completed [3].…”
mentioning
confidence: 99%